Roland Barthes' Semiotic Analysis of Lemonilo Advertising Posters: The Construction of Denotative, Connotative, and Mythical Meanings - Fauziah Amanda Aritonang; Zahwa Safitri Caniago; Bunga Anggraeni; Randi Irwansyah; Nabila Dwi Putri Tarigan; Candri Afrianti Sinabang; Fitri Ervina Tarigan; Tengku Ratna Soraya (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Food product advertising in Indonesia operates as a sign system that constructs meaning and ideology in consumers’ minds. This study analyzes denotative, connotative, and mythological meanings in the advertising poster of Lemonilo Mie Instan Alami Rasa Mie Goreng (Natural Instant Fried Noodles) using Roland Barthes’ semiotic theory. The poster presents a rich sign system: greenish-yellow noodles unlike conventional instant noodles, fresh ingredient toppings (egg, shrimp, chili, mushrooms, vegetables), four green checkmark-verified claims, and the hashtag #KitaSehatKitaHebat. This product contains a semiotic paradox: an instant noodle claiming naturalness and healthiness. This descriptive qualitative study employs Roland Barthes’ semiotic analysis with data from visual observation, documentation, and literature review, analyzed through three stages: denotation, connotation, and myth. Results indicate: (1) denotative level shows literal representation of greenish-yellow noodles with toppings and product claims; (2) connotative level constructs images of naturalness, freshness, and differentiation through visual and verbal elements; (3) mythological level presents a narrative that consuming Lemonilo is an identity act of healthy and achieving individuals. Theoretically, this research enriches semiotic studies of food advertising in Indonesia. Practically, it encourages consumer semiotic literacy and provides insights for producers regarding meaning construction mechanisms in food advertising.